Phytochemical Composition and Antimicrobial Activity of African Walnut (Tetracarpidium conophorum) Oil on Selected Microorganisms Causing Human Skin Infections - Yangomodou, O. D.; Solana, O. I.; Ogungbayi, G. B.; Natalie, Ferry (NIU Journal of Humanities, 2020)
The development of antibiotic-resistant pathogenic strains due to the indiscriminate use of antibiotics has led to search for the use of novel natural antimicrobials in the treatment of human skin infections. The qualitative phytochemical screening and subsequent quantification revealed the presence of bioactive compounds such as alkaloids (3.87 ± 0.02 mg/100 g), saponins (4.37 ± 0.01 mg/100 g), phenol (2.32 ± 0.02 mg/100 g), glycoside (2.66 ± 0.02 mg/100 g), reducing sugar (3.04 ± 0.02 mg/100 g), moderate concentration of flavonoids (1.98 ± 0.02 mg/100 g), minute or trace amount of tannins (0.85 ± 0.02 mg/100 g) and soluble carbohydrate (0.99 ± 0.01 mg/100 g) while terpenoids and hydrogen cyanide were not detected in the nut oil. The assessment of the antimicrobial activity of oil extracted from African walnut ( Tetracarpidium conophorum- Mull. Arg ) was investigated using agar-well diffusion method against clinical isolates of Staphylococcus aureus , Escherichia coli, Cutibacterium acne, Malassezia furfur and Candida albicans which were isolated from human skin infections. The results of the investigation revealed that African walnut oil had inhibitory effect on the growth of all the test microorganisms. Significant differences (p<0.05) were observed in the degree of inhibition of the isolates, but non-significant variations were observed in inhibition among strains of the same species. The most pronounced inhibition as confirmed by the zones of inhibition around growing colonies was on S. aureus. C. acnes was inhibited moderately, growth inhibition of E. coli was mild. Growth inhibition by African walnut oil was not significant (p>0.05) between the two fungal strains. The inhibitory activity of the nut oil was observed to decrease with a decrease in concentration of nut oil in the solvents used, resulting in marked variation in the inhibitory concentration. The implication of this observation is that African walnut oil may be of medical and dermatological importance. Keywords: African walnut oil, Tetracarpidium conophorum, phytochemical screening, antimicrobial activity, skin infections, growth inhibition